Impact of dry, particle-size fractionation on protein and amino acid content of three seaweed species. Issue 1 (31st December 2022) - Healy, Laura E; Zhu, Xianglu; Pojic, Milica; Poojary, Mahesha M; Curtin, James; Tiwari, Uma; Sullivan, Carl; Tiwari, Brijesh K
ABSTRACT: Market demand for "clean and green" food products is increasing, and so there is growing opportunity for the seaweed aquaculture industry to take a position as a key food producer in this area. In this study, in order to investigate the impact of dry fractionation on seaweed protein qualities, dried and milled seaweed powder from three seaweed species was sieved into 6 fractions (F1 to F6) of different particle size from >710 µm to <50 µm. True protein, total protein and amino acid profiles were analyzed to evaluate the protein content and quality of three brown seaweed species commercially harvested in Ireland; Alaria esculenta, Laminaria digitata and Saccharina latissima . In general, A. esculenta had the highest protein content, followed by S. latissima and then L. digitata (4.15 ± 0.12 g/100 g, 2.28 ± 0.1 g/100 g and 1.73 ± 0.01 g/100 g, respectively). Fractionation had a significant impact (p < .01) on protein content, essential amino acid content (p < .05) and non-essential amino acid content (p < .01) across six fractions of seaweed powder within species. F6 (<50 was the fraction that contained the highest protein and amino acid content in both A. esculenta and S. latissima . F1 (>710 µm) contained the highest protein and amino acid content in L. digitata . Glutamic acid was the most prevalent amino acid in A. esculenta and L. digitata (55.34 mg/g and 23.78 mg/g), while aspartic acid was the most prevalent in S. latissima (19.41 mg/g). This information is valuable to both researchers and seaweed producers who can use particle size separation as a simple method to create value-added products using their green biomass for applications across multiple markets. Graphical abstract: uf0001